2006
DOI: 10.1080/13693780600904918
|View full text |Cite
|
Sign up to set email alerts
|

Issues with galactomannan testing

Abstract: Within the past decade detection of the aspergillus antigen galactomannan has become an important and reliable tool for the early diagnosis of invasive aspergillosis. The galactomannan molecule, that is detected by the commercial sandwich ELISA (Platelia Aspergillus, Biorad), was found not to be a single molecule, but a family of molecules that have the epitope that reacts with the monoclonal antibody. Also the cut off level is now world-wide lowered to 0.5 which will help to further standardize and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 37 publications
0
21
1
5
Order By: Relevance
“…Despite their widespread use, recent studies have revealed significant variation in performance. While the specificity of the GM assay is consistently Ͼ85%, the sensitivity of the assay can vary considerably from 29% to 100% and the rate of false-positive reactivity can vary from 5% in adults to 83% in newborn babies (39). Falsepositive results have been attributed to the cross-reaction of MAb EB-A2 with GM from non-Aspergillus fungi (8,12,25,34,39); with galactoxylomannan from Cryptococcus neoformans (5,6); with lipoteichoic acid from intestinal bifidobacteria in the gastrointestinal microbiota of neonates (22); with the cancer prodrug cyclophosphamide (10); and with the GM in food, drink, and infant milk formulas (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their widespread use, recent studies have revealed significant variation in performance. While the specificity of the GM assay is consistently Ͼ85%, the sensitivity of the assay can vary considerably from 29% to 100% and the rate of false-positive reactivity can vary from 5% in adults to 83% in newborn babies (39). Falsepositive results have been attributed to the cross-reaction of MAb EB-A2 with GM from non-Aspergillus fungi (8,12,25,34,39); with galactoxylomannan from Cryptococcus neoformans (5,6); with lipoteichoic acid from intestinal bifidobacteria in the gastrointestinal microbiota of neonates (22); with the cancer prodrug cyclophosphamide (10); and with the GM in food, drink, and infant milk formulas (1).…”
mentioning
confidence: 99%
“…Falsepositive results have been attributed to the cross-reaction of MAb EB-A2 with GM from non-Aspergillus fungi (8,12,25,34,39); with galactoxylomannan from Cryptococcus neoformans (5,6); with lipoteichoic acid from intestinal bifidobacteria in the gastrointestinal microbiota of neonates (22); with the cancer prodrug cyclophosphamide (10); and with the GM in food, drink, and infant milk formulas (1). Contamination of ␤-lactam antibiotics with Penicillium GM may account for the serum reactivity of patients receiving piperacillin-tazobactam or amoxicillin-clavulanic acid (2,20,39,40), although these reports have been disputed (46). There is therefore scope in IA immunodiagnostics for tests that employ MAbs directed at epitopes other than those present on GM.…”
mentioning
confidence: 99%
“…GM testinin duyarlılığının çocuklarda ve erişkinlerde farklılıklar gösterdiği ve aspergillozlu erişkin ve çocuk hastalardaki yalancı pozitiflik oranlarının sırasıyla %3-10 ve %10-44 ve yenidoğanlarda %80 civarında olduğu bildirilmektedir (9). Pediatrik hastalarda ve yeni doğanlarda yüksek yalancı pozitiflik nedeni anne sütünde ve formüla mamalarda yüksek konsantrasyonda bulunan Bifidobacterium bifidum'un çapraz reaksiyonu ya da onların salgıladığı lipoglikan (galaktofuranoz kalıntıları) ile ilişkili olabileceği belirtilmiştir (10,11 …”
Section: Discussionunclassified
“…Such data are therefore supplemented with serological techniques that aim to identify signature molecules (GM and β-glucan) from fungi that are circulating in the patient's serum or that are present in BAL fluids, sputum or urine samples 13 . While these tests display satisfactory sensitivity, they lack sufficient specificity or suffer from interference under certain conditions 1,6 . The LFD test for IPA detection presented here enables the 'point-of-care' diagnosis of IPA and exploits technology that has been used to date in tests for the detection of viruses, bacteria, parasites and toxins [14][15][16][17][18][19] and, most famously, for the home pregnancy tests first introduced by Unipath in 1988.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the development of the Platelia enzyme immunoassay (GM-EIA) that detects Aspergillus galactomannan and a 'pan-fungal' assay (Fungitell test) that detects the conserved fungal cell wall component (1 →3)-β-D-glucan, but not in the mucorales that lack this component in their cell walls 1,4 . Issues surrounding the accuracy of these tests 1,[4][5][6] has led to the recent development of next-generation monoclonal antibody (MAb)-based assays that detect surrogate markers of infection 1,5 .…”
Section: Introductionmentioning
confidence: 99%